Development of biotraps based on Cladophora SP Alga for the biosorption of mercury from environmental waters - Mokone, Joy Gaogakwe (My University, 2018)
Trace metal pollution of environmental waters is a serious ecological concern that causes degradation of water quality in rivers and lakes. Mercury is considered as one of the most toxic trace metals due to its propensity to bioaccumulate in food webs thus causing severe detriment to human health. Biosorption using algae as biosorbents is emerging as a technology for the remediation of trace metal-polluted waters because algae are widely abundant and have high adsorption capacities. Algae can also be immobilized on polymeric supports to enhance their performance, selectivity, and industrial applicability. This work presents the development of novel algal-based biosorbents via the immobilization of Cladophora sp alga in silica gel and alginate beads for the removal of mercury from synthetic aqueous solutions under batch equilibrium and continuous flow modes. Both the modified and unaltered algae were also characterized for biosorption of mercury using several techniques including Fourier Transform Infrared Spectroscopy (FTIR), Braunner-Emmet-Taylor (BET), Scanning Electron Microscopy (SEM) and Electron Dispersive Spectroscopy (EDX). The research also describes a first attempt to elucidate the mechanism for mercury biosorption using pristine and modified forms of Cladophora sp alga. The best performing modified biosorbent (alga immobilized in alginate beads) was also utilized to construct biotraps where were then utilized for mercury removal from acid mine water formed by dissolving salt crusts in deionized water. Batch equilibrium studies revealed that the optimum conditions for metal biosorption were pH 5, 10 g L-1 biosorbent dosage and 25˚C for the modified forms of Cladophora sp alga. However, the equilibrium agitation time and initial metal concentration using the biosorbents were 30 minutes and 100 mg L-1, respectively. The maximum biosorption capacities were 121.3 and 183.4 mg g-1 for the alga immobilized in silica gel and alga immobilized in alginate beads. These biosorption capacities represented removal efficiencies of 82.75 and 86.6%, respectively. Biosorption experimental data also fitted the pseudo-second kinetic model, the Langmuir, and Dubinin-Radushkevich isotherms thus suggesting that biosorption iv occurs on a homogeneous layer and was limited by chemisorptive ion exchange mechanism. Kinetic modeling using the Webber-Morris model showed that intraparticle diffusion was rate limiting only at the start of the biosorption process. Mercury adsorption using the biosorbents involved several functional groups. Chemical modification, FTIR analysis and EDX analysis showed that the amine, sulfonate and carboxyl groups were key players in the mechanism for the biosorption of mercury by the biosorbents. The biosorption process occurred via complex processes wherein ion exchange was the most dominant mechanism. This was confirmed using FTIR analysis, EDX analysis and chemical modification of functional groups on the algal surface. The biosorbents were also effective in retrieving mercury from multi-elemental synthetic aqueous solutions. However, the alga immobilized in alginate beads was more selective for mercury removal than that immobilized in silica gel. Optimal removal under continuous flow operation occurred at 7 cm bed height, 2 mL min-1 flow rate and 2 mg L-1 inlet metal concentration. The column data was also best described by the Bed depth service time, Thomas and Yoon Nelson models. This implied that the service time of the column was proportional to the bed height and external mass transfer and internal diffusion were not the rate limiting mechanisms. Application of the biotraps to acid-impacted environmental waters also significantly reduced the total mercury concentration. The adsorption capacity and removal efficiency obtained were 6.081 mg g-1 and 67.81% respectively. These results demonstrated that Cladophora sp algal-based biotraps have potential for use in remediation technologies for mercury in environmental samples. They can be used to augment wetlands by offering protective screens that will reduce the direct impact of wastewaters flowing through them thus enhancing their longevity.
A Thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy, 2018
Keywords: Green algae; Aquatic weeds--Biological control